Leo Strauss on Jerusalem and Athens - Weber, Gilbert Stanley (My University, 1975)
This thesis attempts to enucleate the thought of Leo Strauss on the relation of Jerusalem and Athens. The specific focus and special interest of this thesis in Leo Strauss' s investigations of Jerusalem and Athens is the relation of Judaism and philosophy.
The essential assertion of Strauss's position is the fundamental and irreconcilable opposition between Jerusalem and Athens. That fundamental opposition is discerned by Strauss chiefly in the classical conception of philosophy and the "metaphysics" of the Bible, and in the contrast of philosophic morality and the morality of the Bible.
Although evidencing change or "development," Strauss's thought remains centrally concerned with "das theologisch-politische Problem." His early work on Maimonides and his Islamic predecessors, Philosophic und Gesetz, exhibits his concern with the relation of political philosophy and theology, exotericism, the relation of the Law and the natural law, the quarrel between ancients and moderns, the distorting effect of reading pre-modern writers through modern lenses and the inadequacy of modern philosophies of Judaism. The extent and character of Strauss's "development," as well as the abiding unity of his vision, is indicated in viewing his earlier understanding in light of his own later "corrections."
The thesis concludes with Strauss's thematic elaboration of the insufficiency generally of Enlightenment and post-Enlightenment accommodations of Jerusalem and of modern Jewish "movements," in particular.
What is all important to this thesis is the central fact of Strauss's life-long attention to Jerusalem and Athens, to "das theologisch-politische Problem," to Judaism and philosophy. Attention is the essence of the "third alternative" to unreasoned belief and unreasoned unbelief.
Keywords: Religion; Religion